The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnins.2021.679199
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament Light Chain as Biomarker for Amyotrophic Lateral Sclerosis and Frontotemporal Dementia

Abstract: Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are two related currently incurable neurodegenerative diseases. ALS is characterized by degeneration of upper and lower motor neurons causing relentless paralysis of voluntary muscles, whereas in FTD, progressive atrophy of the frontal and temporal lobes of the brain results in deterioration of cognitive functions, language, personality, and behavior. In contrast to Alzheimer’s disease (AD), ALS and FTD still lack a specific neurochemical bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 102 publications
(353 reference statements)
2
60
0
1
Order By: Relevance
“…We subsequently tried to perform a second search for studies relating to FTD; however, the number of studies found was too small to allow a meta-analysis to be performed. It should also be mentioned that the clinical, pathological, and genetic features of FTD exhibit marked heterogeneity [ 37 ]. Furthermore, the prevalence of FTD is lower than that of AD, which affects subject recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We subsequently tried to perform a second search for studies relating to FTD; however, the number of studies found was too small to allow a meta-analysis to be performed. It should also be mentioned that the clinical, pathological, and genetic features of FTD exhibit marked heterogeneity [ 37 ]. Furthermore, the prevalence of FTD is lower than that of AD, which affects subject recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prevalence of FTD is lower than that of AD, which affects subject recruitment. Further studies of FTD are needed, and identifying other markers of the disease, such as neurofilament light chain, would also be helpful [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulations of neurofilaments are a pathological feature of several neurodegenerative diseases ( Didonna and Opal, 2019 ), including amyotrophic lateral sclerosis (ALS), Alzheimer’s, and Parkinson’s diseases. Moreover, NFL as a highly abundant protein in neurons shows promise as a serum biomarker for neuronal disruption in various neurological diseases, such as ALS ( Verde et al, 2021 ) and multiple sclerosis ( Ferreira-Atuesta et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to serving as therapeutic targets, these cryptic exon inclusion events can simultaneously be harnessed as biomarkers for diagnosis and prognosis and for evaluating the efficacy of experimental therapeutics 11 . In ALS, several candidate fluid biomarkers have been reported, such as vascular endothelial growth factor (VEGF), 37 neurofilament light chain protein (NfL) 38 and urinary p75 ECD 39 . However, because these likely reflect neurodegeneration in an unspecific way, rather than being specific to ALS or FTD, none of them is definitive 40,41 .…”
Section: Cryptic Exons As Novel Biomarker Candidatesmentioning
confidence: 99%